HUBUNGAN ANTARA MINAT BELAJAR DENGAN KEBERHASILAN BELAJAR SISWA DENGAN PENERAPAN BUKU AJAR ELEKTRONIK SISTEM EKSKRESI BERBASIS BRAIN-BASED LEARNING (BBL) DILENGKAPI VIDEO DAN DIAGRAM ROUNDHOUSE - Ratna Putri Aulia; Jekti Prihatin; Bea Hana Siswati (Universitas Lancang Kuning, 2023)
This study aims to investigate the relationship between students' learning interest and student learning success in the application of the Brain-Based Learning (BBL) based Excretion System electronic textbook equipped with videos and Roundhouse diagrams. The research method used is a survey method with correlation techniques. The population in this study were students at SMAN 1 Grati Pasuruan, and the sample consisted of class X students at SMAN 1 Grati Pasuruan Indonesia. Data was collected through pretest and post test to measure students' learning interest and student learning success. The results showed that there was a significant positive relationship between students' learning interest and student learning success. In addition, the application of the BBL-based Excretory System electronic textbook which is equipped with videos and Roundhouse diagrams also shows a positive influence on student learning success. Therefore, the use of BBL-based Excretory System electronic textbooks equipped with videos and Roundhouse diagrams can increase student learning interest and learning success in the Excretion System subject.